Overview of Cannabis including Kampo Medicine and Therapy for Treatment of Dementia: A Review - Wenger, Tibor; Watanabe, Kazuhito; Sasaki, Yui; Kanazawa, Keiko; Shimizu, Koichi; Sirikantaramas, Supaart; Shoyama, Yoshinari; Taura, Futoshi; Morimoto, Satoshi; Shoyama, Yukihiro (Frontiers in Pharmacology, 2022)
Cannabis sativa L. is an annual herb oldest cultivated plants as a source of fiber since about 5000 B.C. On the other hand, the cannabis flower and seed are listed in Shennong’s classic Materia Medica approximately 2000 years ago. The formulas prescribed with cannabis in Kampo medicine have been summarized. Cannabidiol (CBD) and tetrahydrocannabinol (THC) are the major neurological and psychiatric cannabinoids, and develop to drugs. It becomes evident that the therapeutic CBD and/or THC are the important candidate of anti-dementia drugs having different mechanism for Alzheimer’s patients. Two receptors and endocannabinoids are also discussed for underlying mechanism of action. In order to promote the breeding of cannabis plant containing higher concentration of target cannabinoid the biosynthetic enzymes were isolated, cloning and the tertiary structure of THCA synthase determined by x-ray analysis resulting in the possibility of molecular breeding for cannabinoids.